2014
DOI: 10.1017/jfm.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte responses in low-shear-rate flows: effects of non-biconcave stress-free state in the cytoskeleton

Abstract: Inspired by the recent experiment on erythrocytes (red blood cells, RBCs) in weak shear flows by Dupire et al. conduct a numerical investigation to study the dynamics of RBCs in low-shear-rate flows by applying a multiscale fluid-structure interaction model. By employing a spheroidal stress-free state in the cytoskeleton, we are able to numerically predict an important feature, namely that the cell maintains its biconcave shape during tank-treading motions. Furthermore, we numerically confirm the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 61 publications
(95 reference statements)
8
65
2
Order By: Relevance
“…A key consistency check is to determine whether the motions are qualitatively consistent with the applied shear stresses. Although the motion of RBCs has been the subject of extensive simulation and computational efforts, [42][43][44][45][46] little work has examined the motion of RBCs entering a constriction as tested here. In the absence of detailed predictions, we instead examine the limiting case of perfectly rigid ellipsoids.…”
Section: Rigid Body Theorymentioning
confidence: 99%
“…A key consistency check is to determine whether the motions are qualitatively consistent with the applied shear stresses. Although the motion of RBCs has been the subject of extensive simulation and computational efforts, [42][43][44][45][46] little work has examined the motion of RBCs entering a constriction as tested here. In the absence of detailed predictions, we instead examine the limiting case of perfectly rigid ellipsoids.…”
Section: Rigid Body Theorymentioning
confidence: 99%
“…It is similar to the methods developed by Bagchi et al (Cordasco, Yazdani & Bagchi, 2014;Yazdani, Kalluri & Bagchi, 2011). It should be noted that some other methods are also developed to model RBCs under flow such as the particle-based model (Fedosov et al, 2011a;Fedosov et al, 2011b) and the three-level multiscale structural model (Peng, Mashayekh & Zhu, 2014;Peng & Zhu, 2013). In the front tracking method, the cell membrane is discretized into a set of triangular planar elements ( Fig.…”
Section: Model and Methodsmentioning
confidence: 98%
“…In most computational studies, the reference shape is assumed to be a biconcave disk, 47,108,129,138 and several important RBC dynamics, such as tank-treading, tumbling, and swinging motions in simple shear flow, can be simulated using this assumption. Peng et al 113 also numerically investigated RBC dynamics in shear flow using a multi-scale membrane model. The authors assumed a spheroidal stress-free shape in the cytoskeleton, instead of a biconcave shape, and reported that the cell maintained its biconcave shape during the tank-treading motion at a low shear rate.…”
Section: Mechanical Modeling Of the Rbc Membranementioning
confidence: 99%
“…A BEM is now widely used for cellular flow. 47,108,113,129 This method can explicitly treat viscous stress jump across the membrane, and is one of the most accurate computational schemes for tracking the interface. However, BEM is limited to a Stokes flow regime, and it is difficult to discuss an inertia effect.…”
Section: Hemodynamics In Microvesselsmentioning
confidence: 99%